Clinicopathologic Parameters of Peritoneal Fluid as Predictors of Gastrointestinal Lesions, Complications, and Outcomes in Equine Colic Patients: A Retrospective Study - Emily Martin; Kate Sarkan; Austin Viall; Shannon Hostetter; Kira Epstein (Animals)
Neutrophil characteristics in peritoneal fluid (PF) may aid in diagnosing and treating specific colic lesions and complications. The objective of this retrospective study was to evaluate quantitative PF leukocyte values, as well as PF total protein (TP) and lactate, for associations with diagnosis, morbidity, and mortality in horses with acute colic. Three hundred and forty-two horses that presented to one institution between January 2010–2020 for the evaluation of acute colic were included. The PF total nucleated cell count (TNCC), % and total neutrophil counts, total protein (TP), and lactate were analyzed for associations with lesion location and type, the development of postoperative reflux (POR) or systemic inflammatory response syndrome (SIRS), and survival to discharge via Kruskal–Wallis testing. Horses with strangulating lesions had higher PF % neutrophils, neutrophil count, and TNCC compared to non-strangulating lesions. The development of SIRS or POR was associated with higher PF TNCC, total neutrophil count, TP, and lactate. Horses that did not survive to discharge had increased PF % neutrophils, neutrophil count, TP, lactate, and ratio of PF-to-systemic TP than those that survived via univariable analysis. Identified associations between increased PF neutrophils and the development of POR and SIRS warrant further investigation to better understand their role in the pathogenesis of equine colic and potential as targets for therapeutic intervention.